Breast Implant-Associated Anaplastic Large Cell Lymphoma: Two Distinct Clinical Presentations - Miranda, Pedro (2022)
Breast implant-associated anaplastic large cell lymphoma (BIA-ALCL) is a rare CD30 positive T cell lymphoma whose incidence has recently increased. Until 2020, 733 cases of BIA-ALCL and 36 deaths have been reported around the world, with only one confirmed case in Portugal. The authors describe two clinical cases of BIA-ALCL after breast cancer reconstruction using macrotextured implants. Case 1: A 45-year-old patient, who presented with a typical late-onset seroma five years after breast reconstruction and underwent capsulectomy, confirming localized disease to the capsule. Case 2: A 43-year-old patient presented with an atypical presentation of pleural effusion and tumor mass, 14 years after reconstruction. She underwent implant removal and chemotherapy, due to metastatic disease. These clinical cases illustrate two very distinct clinical presentations of BIA-ALCL. Early diagnosis of this entity allows for effective treatment of the disease, which should be approached in a multidisciplinary setting.